Heuristic Approaches to solve a Generalized Dial-a-Ride Problem Applied to Car-pooling. Issue 12 (2016) - Pinson, Corentin; Afsar, H. Murat; Prodhon, Caroline
Abstract: In this paper, we present a metaheuristic method to address a Generalized Dial-a-Ride Problem applied to car-pooling (or ride sharing) case. Car-pooling is the sharing of car journeys so that more than one person travels in a car. Appearing in 1940s as a result of oil shortage, car-pooling, becomes more and more popular, especially in the last decade thanks to massive use of internet. The number of web sites proposing car pooling increases constantly but they merely offer a meeting platform for different actors. The aim of this work is to propose an optimization scheme which can be deployed in such sites. Tests on instances with up to 50 requests and 15 drivers on a graph with 433 nodes show the efficiency of the methods and the necessity of such an optimization tool.